Floristic Composition, IUCN Status and Ayurvedic Importance of Flora Documented in North Sikkim District of Sikkim State - Pulicherla, Yugandhar; Cheemanapalli, Srinivasulu; Taboh, Mumtam; Nagayya, Shiddamallayya; Bora, Devanjal; Bhardwaj, Yashpal; Mandal, Tushar Kranthi; Anku, Gyati; Bhuyan, Gurucharan; Singh, Kamaleswar; et al. (Indian Forester, 2024)
The Himalayan state Sikkim is the homeland of 26% of flowering plants in India. Among the state, the North Sikkim district has dense vegetation and a vast diversity of flora. The present study intended to conduct floristic exploratory studies in the North Sikkim district according to the protocols provided by the Central Council for Research in Ayurvedic Sciences (CCRAS), New Delhi. The collected plant specimens were subjected to the preparation of Herbarium using standard techniques, and taxonomic identification was carried out using different floras. The IUCN Red List database was used to evaluate the threatened status of explored plant species. The ayurvedic importance and trade value of explored plants were verified with standard literature. This survey reported 120 plant species belonging to 106 genera and 56 families. Piper and Trichosanthes are among the genera, and Asteraceae among the families are most abundant. The IUCN red list data revealed that 71% of plant species are in the â€œNot Evaluatedâ€ category. Among the 120 plants, 14 plant species are reported in Ayurvedic texts, and 18 plants are reported to have good trade value in the Indian traditional market. This floristic exploratory data represents species richness in geographical areas and the diversity of flora in the North Sikkim district. It may help researchers to identify, collect, and validate specific plant species for future research studies.